Energy Policy on National Defense: Oil and Gas Exploration in the Sebatik Island Region - Rizalah, Taufik; Khaerudin, Khaerudin; Yanto, Sri; Ronika, Yulia Febi Zita (CV. Rayyan Dwi Bharata, 2025)
Oil and gas exploration on Sebatik Island is important for Indonesia's energy policy and national defense. Oil and gas potential in the region can increase national energy supply and reduce dependence on energy imports. In addition, Sebatik Island's strategic location on the border strengthens national security. This study aims to examine the impact of oil and gas exploration in Sebatik Island on energy policy and national defense. The approaches used are energy security theory and national security theory, which explore the diversification of energy sources and the role of energy infrastructure in supporting defense strategies. The results show that oil and gas exploration on Sebatik Island can improve energy security and support national defense strategies. In addition, this exploration can potentially improve the local economy through employment and foreign investment.